Risk factors and clinical prediction models for low-level viremia in people living with HIV receiving antiretroviral therapy: an 11-year retrospective study - Zhang, Wenhui; Shi, Jinchuan; Wang, Ying; Li, Er; Yan, Dingyan; Zhang, Zhongdong; Zhu, Mingli; Yu, Jianhua; Wang, Yi (Frontiers in Microbiology, 2024)
Objective This study explores the risk factors for low-level viremia (LLV) occurrence after ART and develops a risk prediction model. Method Clinical data and laboratory indicators of people living with HIV (PLWH) at Hangzhou Xixi Hospital from 5 April 2011 to 29 December 2022 were collected. LASSO Cox regression and multivariate Cox regression analysis were performed to identify laboratory indicators and establish a nomogram for predicting LLV occurrence. The nomogram’s discrimination and calibration were assessed via ROC curve and calibration plots. The concordance index (C-index) and decision curve analysis (DCA) were used to evaluate its effectiveness. Result Predictive factors, namely, age, ART delay time, white blood cell (WBC) count, baseline CD4+ T-cell count (baseline CD4), baseline viral load (baseline VL), and total bilirubin (TBIL), were incorporated into the nomogram to develop a risk prediction model. The optimal model (which includes 6 variables) had an AUC for LLV after 1-year, 3-year, and 5-year of listing of 0.68 (95% CI, 0.61–0.69), 0.69 (95% CI, 0.65–0.70), and 0.70 (95% CI, 0.66–0.71), respectively. The calibration curve showed high consistency between predicted and actual observations. The C-index and DCA indicated superior prediction performance of the nomogram. There was a significant difference in CD4 levels between LLV and non-LLV groups during the follow-up time. The dynamic SCR, ALT, TG and BG levels and occurrence of complications differed significantly between the high- and low-risk groups. Conclusion A simple-to-use nomogram containing 6 routinely detected variables was developed for predicting LLV occurrence in PLWH after ART.